Anaesthetists' knowledge of appropriate adrenaline administration in three clinical scenarios - Anamourlis, Prodromos Christopher (My University, 2016)
Lack of knowledge and clinical experience in the event of an emergency are a lethal combination. Adrenaline is the drug of choice for resuscitation during cardiovascular collapse. Incorrectly dosing patients with adrenaline can lead to death by overdose or by undertreating the emergent condition. This highlights the importance, not only of resuscitation protocols but also the physician’s knowledge of and adherence to such guidelines. Research has consistently shown that physicians commonly make dosing mistakes during emergencies concerning adrenaline. Identifying whether or not this is due to a deficit in knowledge is important in understanding how to improve the outcomes of patients in such emergencies. The aim of this study was to determine the knowledge of anaesthetists working in the Department of Anaesthesiology at the University of the Witwatersrand regarding the appropriate administration of adrenaline for anaphylaxis, cardiac arrest and inotropic infusions. This was a prospective, contextual, descriptive study on a sample of anaesthetists working in the Department of Anaesthesiology at the University of the Witwatersrand. Anaesthetists who were willing to participate in the study were given a brief introduction to the study and a questionnaire to complete regarding adrenaline doses in three different clinical scenarios. Data collection took place during February 2014 and June 2014. Anaesthetists’ knowledge of adrenaline was analysed using descriptive and inferential statistics. The knowledge of Wits anaesthetists regarding adrenaline use in cardiac arrest, anaphylaxis and as an infusion, is inadequate. A total of 104 anaesthetists answered the questionnaire (n=104). The pass rate for the questionnaire was 14% (n=15). The median score for the questionnaire was 50%. A statistically significant difference was found between the pass rates of those anaesthetists who had attained an ACLS course and those who had not (p=0.0339). A weak correlation was found between anaesthetists knowledge and years of anaesthetic experience (r=0.2460). When comparing the knowledge of anaesthetists between different professional designations, a statistically significant difference was found between the intern groups’ knowledge and the consultants (33% vs 67%: p=0.0013). The study questionnaire uncovered major knowledge deficits in Wits anaesthetists, and revealed that ACLS certification improved knowledge in anaesthetists. This study warrants educational intervention and future investigation into knowledge improvement.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Anaesthesiology, Johannesburg, 2015
Keywords: Adrenaline Admistration; Epinephrine; Anesthetists